THE GAMBANG KROMONG, CHINESE BENTENG’S IDENTITY IN TANGERANG - Reza Apriliani Putri; C. Dewi Hartati (Fakultas Sastra Universitas Darma Persada, 2022)
This article discusses the art of Gambang kromong which is a form of identity for the Chinese Benteng in Tangerang. This art is a form of acculturation of two cultures, Chinese and Betawi cultures. The research method used is a qualitative research method, namely literature study, documentation, observation, and interviews with informants who know about Gambang Kromong. The result of this study is to explain the efforts to preserve the art of Gambang Kromong so that it can be maintained it can become a form of identity for the Chinese Benteng in Tangerang.